Analisis Kinerja Keuangan Menggunakan Metode Vertikal pada Ultrajaya Milk Industry & Trading Company Tbk (Studi pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2022 dan 2023) - Astro Yudha Kertarajasa (Teewan Journal Solutions, 2025)
Qualitative descriptive research is the kind of study that this is. The objectives of this study are to comprehend and evaluate Ultrajaya Milk Industry & Trading Company Tbk's (Ultrajaya) financial performance using a vertical analysis approach. The financial records of Ultrajaya Milk Industry & Trading Company Tbk (Ultrajaya) for the years 2022 and 2023, with a sample of two years, comprise the population of this study. The outcomes of Ultrajaya Milk Industry & Trading Company Tbk, Tbk's vertical analysis of its balance sheet for the years 2022–2023 are ideal. The total assets post, which is higher than the total liabilities post, illustrates this. This indicates that the corporation has sufficient assets to pay off all of its debts and still has assets left over after that. This indicates that the business has a healthy margin of safety and sound financial standing. The profit and loss report's vertical analysis reveals that operational expenses have grown dramatically and have an impact on operating profitability. The profit for the year has improved significantly despite an increase in the cost of products sold. All things considered, the year-over-year growth in profit is indicative of strong financial performance and offers numerous advantages to the business, such as raised share value, dividend payments, and greater flexibility with regard to debt and investment management. In summary, Ultrajaya Milk Industry & Trading Company Tbk Tbk exhibits excellent financial performance.